2016
DOI: 10.1080/07357907.2016.1242597
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perspectives and Practice Patterns Toward Opportunistic Salpingectomy in High- and Low-Risk Women

Abstract: We identified broad support and factors limiting willingness to perform OBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
2
19
1
3
Order By: Relevance
“…Thus, improvement in knowledge of current literature might increase implementation rate. Despite our findings, Jones et al [15] investigated the implementation of OS and found no association between practice patterns and physicians characteristics. This discrepancy could be explained by differences in the subset of analyzed characteristics or study population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, improvement in knowledge of current literature might increase implementation rate. Despite our findings, Jones et al [15] investigated the implementation of OS and found no association between practice patterns and physicians characteristics. This discrepancy could be explained by differences in the subset of analyzed characteristics or study population.…”
Section: Discussioncontrasting
confidence: 99%
“…Currently there is no consensus regarding OS in the Netherlands, resulting in a large variety of practice, probably due to a lack of clear guidelines. According to previous research in other countries, 43%–77% of gynecologists discuss the possibility of an OS [131415]. It is likely that the adoption rate is influenced by several factors, which can be found on different levels, such as the innovation itself (OS), the organization of care, healthcare professionals attitudes towards OS and characteristics of the individual patient [16].…”
Section: Introductionmentioning
confidence: 99%
“…6e9 Nonetheless, many obstetrician/gynecologists have adopted salpingectomy with cesarean delivery. 10 Removal of the fallopian tubes may decrease the risk of ovarian cancer by as much as 70%, which is more than the risk reduction attributed to tubal ligation (26e34%). 11e14 Salpingectomy appears to be safe 15,16 and cost-effective 12,17 with hysterectomy or interval sterilization.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this shift towards removal of the Fallopian tubes during ovarian-sparing hysterectomy, a large percentage of women do continue to retain their Fallopian tubes after hysterectomy. It was estimated that 15.8% of ovarian-sparing hysterectomies in 2013 underwent bilateral salpingectomy [9] and a recent study by Jones et al, reported that only 23% of the gynecologists surveyed understood the cancer risk-reduction associated with bilateral salpingectomy [10]. Therefore it is still important for radiologists to be aware of the potential of a dilated fluid-filled Fallopian tube remnant, or hydrosalpinx, as a potential complication of ovarian-sparing hysterectomy [11] since these cystic structures can be mistaken for a cystic adnexal neoplasm.…”
Section: Introductionmentioning
confidence: 99%